Everyday memory difficulties in children and adolescents with Fetal Alcohol Spectrum Disorder. (3rd October 2019) - Agnihotri, Sabrina; Subramaniapillai, Sivaniya; Keightley, Michelle; Rasmussen, Carmen; Cameron, Debra; Ryan, Jennifer; Rovet, Joanne
ABSTRACT: Purpose : To investigate whether significant differences exist in everyday memory between youth with Fetal Alcohol Spectrum (FASD) compared with a nonexposed (NE) control group, while controlling for socioeconomic status and other comorbidities. Methods : Caregiver ratings using the Everyday Memory Questionnaire were obtained for 105 youth (9–17 years of age). Scores were compared between youth with a FASD diagnosis ( N = 41; 56% male) and the NE group ( N = 64; 53% male) using multivariate analysis of variance. Results : Significantly poorer scores were found across all domains of everyday memory in youth with FASD ( p <0.01 for all comparisons). Findings maintained significance after controlling for group differences in socioeconomic status, presence of learning, and attention disorders, as well as exposure to other teratogens. Conclusions : This study provides important insights regarding the memory issues that underlie daily functional challenges faced by youth with FASD and the need for future intervention research.